2004
DOI: 10.1200/jco.2004.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide for the Treatment of Brain Metastases Associated With Metastatic Melanoma: A Phase II Study

Abstract: Temozolomide was well tolerated and demonstrated activity in the treatment of brain metastases from MM. Further evaluation of temozolomide combination therapy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
162
1
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(177 citation statements)
references
References 24 publications
5
162
1
9
Order By: Relevance
“…An important observation in this study is that the median survival from starting chemotherapy was 2 months, which emphasises the very poor prognosis of patients with brain metastases from melanoma, even with good performance status. This figure is similar to the median overall survival of 3.2 months reported in the largest clinical trial of patients (N ¼ 151) with brain metastases from melanoma reported to date (Agarwala et al, 2004). It could be argued that restaging patients after three cycles of treatment (as opposed to two cycles) in the study reported here may have underestimated the response rate, but this would be true only for very short-lived responses, which would be of questionable clinical significance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…An important observation in this study is that the median survival from starting chemotherapy was 2 months, which emphasises the very poor prognosis of patients with brain metastases from melanoma, even with good performance status. This figure is similar to the median overall survival of 3.2 months reported in the largest clinical trial of patients (N ¼ 151) with brain metastases from melanoma reported to date (Agarwala et al, 2004). It could be argued that restaging patients after three cycles of treatment (as opposed to two cycles) in the study reported here may have underestimated the response rate, but this would be true only for very short-lived responses, which would be of questionable clinical significance.…”
Section: Discussionsupporting
confidence: 82%
“…The brain is a common site of metastasis in melanoma and the standard treatment for brain metastases is radiotherapy although surgery has a role in selected patients. Dacarbazine is generally ineffective at treating brain metastases from melanoma although a response rate of 7% with a further 29% of patients experiencing disease stabilisation has been reported with the related orally administered alkylating agent temozolomide as a single agent (Agarwala et al, 2004). Temozolomide is associated with a response rate of 13 -25% in the treatment of metastatic melanoma outside the brain and is generally well tolerated with myelosuppression the major toxicity (Bleehen et al, 1995;Middleton et al, 2000;Bafaloukos et al, 2005;Kaufmann et al, 2005).…”
mentioning
confidence: 99%
“…The observed response rate of 9% and the stabilization of !11% of brain metastases in the current study are in line with the treatment results from a Phase II trial of temozolomide for brain metastases from melanoma that, similar to the current study, did not require immediate irradiation and showed a response rate of 6% and a stabilization rate of 26%. 13 Patient-or disease-related characteristics that distinguished patients with control of neurologic disease from nonresponders could not be demonstrated in the current study. Therefore, stabilization or response of extracranial metastatic melanoma to temozolomide was the only predictor of control of neurologic disease.…”
Section: Toxicitymentioning
confidence: 57%
“…11 Temozolomide is an analogue of dacarbazine that has excellent oral bioavailability and relatively high central nervous system (CNS) penetration. A large Phase II study of temozolomide for patients with brain metastasis from melanoma 13 who did not require immediate RT showed that temozolomide was tolerated well and produced an overall objective response rate of 6% and a stable disease (SD) rate of 26%, which is comparable to the response in patients with visceral extracranial metastasis. In the current study, we assessed the response of brain metastasis in patients who showed a response to temozolomide of systemic metastatic disease, and we evaluated whether it is feasible to defer or possibly withhold cranial RT.…”
mentioning
confidence: 98%
“…Topoisomerase I (topotecan, irinotecan) and II (etoposide, teniposide) inhibitors as well as platinum-based agents (cisplatin, carboplatin) are used for the treatment of lung cancer brain metastases (8), alkylating drugs such as dacarbazine, TMZ or nitrosoureas are used against melanoma or breast cancer manifestations in the brain (9,10). Of note, there is no specific chemotherapeutic agent for the treatment of brain metastases.…”
Section: Introductionmentioning
confidence: 99%